1979
DOI: 10.1038/bjc.1979.116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carrageenan, PVP and tumour-bearer serum on immunity induced by excision or mitomycin C-treated tumour cells in mice

Abstract: Summary.-Carrageenan (Cg) was tested for its effects on the growth of, and immunity to, 2 methylcholanthrene-induced syngeneic murine fibrosarcomas (HI and H2). The tumours were found not to share major tumour-specific transplantation antigens. H2 appeared more immunogenic than HI. In contrast to HI, immunity induced by H2 was not affected by Cg, nor was its growth in Cg-treated normal mice augmented. We propose that TBS does not inhibit CMI in vivo provided that macrophages remain functional, but may do so wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Similar observations have been made by others (Kearney et al, 1979) who demonstrated that carrageenan abolished the weak immunity for H1 tumor cells produced by previous excision of the tumor but had no effect on the stronger immunity induced by mitomycin-C-treated H1 cells. The tumor growth in carrageenan-treated tumor-excised mice was significantly greater than the growth in carrageenan-treated normal mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar observations have been made by others (Kearney et al, 1979) who demonstrated that carrageenan abolished the weak immunity for H1 tumor cells produced by previous excision of the tumor but had no effect on the stronger immunity induced by mitomycin-C-treated H1 cells. The tumor growth in carrageenan-treated tumor-excised mice was significantly greater than the growth in carrageenan-treated normal mice.…”
Section: Discussionsupporting
confidence: 88%
“…The tumor growth in carrageenan-treated tumor-excised mice was significantly greater than the growth in carrageenan-treated normal mice. They (Wu and Kearney, 1979) have also suggested that the stimulation of the growth of small tumor inocula by tumor fragments or non-viable cells was due to the reduced clearing of viable tumor cells by macrophages and that carrageenan stimulated tumor growth by removing macrophages. Thus it is possible that macrophages are required for non-specific tumor-cell clearance and that carrageenan simply reduces this function.…”
Section: Discussionmentioning
confidence: 99%